Hubungan Usia dan Jenis Kelamin dengan Jenis Kelainan Refraksi pada Anak di Pusat Mata Nasional Rumah Sakit Mata Cicendo (Pusat Mata Nasional Rumah Sakit Mata Cicendo Bandung, 2021)
Introduction: Refractive disorder is one of the most common causes of visual impairment worldwide and becomes the second leading cause of blindness that can be cured. Uncorrected refractive error is the leading cause of vision impairment in children. An estimated 12,8 million children 5 to 15 years of age worldwide are affected. Purpose: To describe the correlation between age and sex with the refractive disorder in National Eye Center, Cicendo Eye Hospital on January ? December 2015. Method: An analytical observational study. The subjects were children diagnosed with refractive disorders based on medical records at the pediatric ophthalmology and strabismus department in Cicendo Eye hospital. The data analyzed using chi-square (x2) with significances of p lebih kecil 0.05. Results: We found 1684 refractive error patients; 41.9% are boys and 58.1% girls. It mainly happened in 11-15 years of age (52.9%). Simple myopia and compound myopic astigmatism are mostly found in girls aged 11-15 years old. Simple hypermetropia and simple myopic astigmatism are primarily in boys aged 6-10 years old, and compound hypermetropic astigmatism in boys 0-5 years old. Conclusion: Recognition of any refractive error in children is a major step in preventing childhood vision loss, a significant public health problem. There is a correlation between age and sex with the refractive disorder (p lebih kecil 0.05). Keywords: refractive disorders, children, visual impairment..